2009
DOI: 10.1111/j.1468-1293.2008.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of cavitary lung lesions in patients with HIV infection*

Abstract: Although many studies have been carried out on pulmonary diseases in HIV-infected patients, studies specifically investigating the aetiologies of cavitary lung lesions are rare. MethodsHIV-infected patients enrolled in a cohort study who presented with cavitary lung lesions by radiography were identified between June 1994 and March 2008. Medical records and radiological and microbiological data for these patients were retrospectively reviewed using a standardized case collection form. ResultsDuring the 14-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Nevertheless, pulmonary nodular lesions with or without cavitation, although reported in other studies, were not recognized as common manifestations of HIV-associated PC [6, 7, 10]. More recently, Lin et al reported that PC contributed to about 17% of the cavitary pulmonary lesions in HIV-infected patients [11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, pulmonary nodular lesions with or without cavitation, although reported in other studies, were not recognized as common manifestations of HIV-associated PC [6, 7, 10]. More recently, Lin et al reported that PC contributed to about 17% of the cavitary pulmonary lesions in HIV-infected patients [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Also, penicilliosis was unlikely considered because our patients were not from an endemic area and did not have skin lesions or blood culture results consistent with penicilliosis. Aside from fungal infections, pulmonary nodules could also be caused by many other reasons, such as mycobacteria infection and malignancy [11, 13, 20–22], and those etiologies should be included in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11 patients with dyspnea 5 also had lung lesions, of these one was diagnosed with Pneumocystis jiroveci and non with tuberculosis. Lung involvement of P. marneffei has been shown in Taiwan where it was found to be the most common cause of cavities in the lungs of immunosuppressed HIV infected patients [10]. The majority of patients with dyspnea did not have lung lesions, hence the dyspnea might be due to the severe condition with multi-organ involvement and acute respiratory distress syndrome (ARDS).…”
Section: Discussionmentioning
confidence: 99%
“…on May 12, 2018 by guest http://cmr.asm.org/ cells/l should prompt a search for other etiologies (33,102,161,210). Although pulmonary TB is the most common presentation regardless of the stage of HIV infection, persons with advanced immune suppression are more likely to have extrapulmonary TB than are HIV-infected persons with relatively intact immunity or persons without HIV (15,33,83,136).…”
mentioning
confidence: 99%